Anthropometric Indicators and Type 2 Diabetes Mellitus Among Older Adults in a Primary Care Setting - Safrina Oksidriyani; Putri Tiara Rosha; Refani Alycia Kusuma; Anastu Regita Nareswara; Nur Ahmad Habibi; Bintang Rizqi Kurniawan; Ela Sri Faniyanti; Bela Prasasti (Penerbit Goodwood, 2026)
Purpose: This study aimed to evaluate the association between five anthropometric indicators and type 2 diabetes mellitus (T2DM) prevalence among older adults in a primary care setting in Semarang, Indonesia. Research Methodology: A cross-sectional study enrolled 55 individuals aged ?45 years at Kedungmundu Primary Health Center. Anthropometric measurements and capillary blood glucose were collected from routine health examinations. T2DM was defined as random blood glucose ?200 mg/dL or prior diagnosis. Independent t-tests, Mann–Whitney U tests, and multivariate logistic regression were applied. Results: Of 55 participants (mean age 59.95 ± 6.76 years; 9.1% T2DM), no significant differences were found in any anthropometric indicator (all p > 0.05), although WC (92.00 vs. 89.50 cm), BMI (29.33 vs. 26.28 kg/m²), WHtR (0.61 vs. 0.58), and BRI (5.86 vs. 5.15) were consistently higher in the DM group. Multivariate analysis identified age as the only variable approaching significance (OR = 0.87, 95% CI: 0.75–1.01, p = 0.062), suggesting T2DM was more frequent among younger elderly individuals. Conclusions: Consistent directional trends support the exploratory utility of WC, BMI, and WHtR as initial metabolic screening tools in primary care for younger elderly individuals, pending confirmation through larger longitudinal studies. Limitations: The small DM case count (n = 5), cross-sectional design, and single-site recruitment limit statistical power and generalizability. Contributions: This study provides original evidence on the utility of five anthropometric screening indicators for T2DM risk identification in elderly Indonesian primary care populations, informing clinical practice and screening strategies in resource-limited health settings.